Competitive statebuilding from the demand-side: counter-state services and civilian choice in Kosovo, 1989-1998. Issue 3 (4th May 2022) - Madison, Ian
ABSTRACT: Counter-state actors often supply services to foster civilian support. Yet little work explores the civilian 'demand-side' of this interaction. This paper examines how civilians navigated between overlapping state and counter-state services during a case of non-violent competitive statebuilding. Between 1989 and 1998, a Kosovar-Albanian 'parallel state' provided education, healthcare, and justice as part of a strategy to secede from Serbia. It finds that two factors are key: the level of group solidarity individuals are subject to, and the unique characteristics of the services they are receiving. Increased group solidarity constrains how individuals decide between providers, yet the extent to which this impacts choice depends on the characteristics of different services. Education is collectively delivered and tied to nation-building; decisions depend on social norms. Healthcare is individual and immediate; decisions are rooted in trust. Justice varies between discreet civil cases where people can 'shop around', and criminal cases, which can comprise highly visible, collective events with significant social pressure. Understanding how solidarity and service characteristics intersect is key to understanding the demand-side of competitive statebuilding.